THE EFFECTIVENESS OF BLENDED LEARNING-BASED LEARNING METHODS IN PIP VIOLIN SUBJECTS AT SMK NEGERI 8 SURAKARTA - Witantri Catri Daniswari; Irfanda Rizki Harmono Sejati (LPPM Institut Seni Indonesia Padangpanjang, 2023)
Learning in Indonesia has experienced the impact of changes in learning activities due to the Covid-19 pandemic which has been spreading for around two years. The obvious change happen is in the learning process itself, some of the efforts that teachers has to prepare, such as adjusting the learning strategies and the learning methods accordingly.The purpose of this study is to describe the application of PIP violin learning with blended learning-based methods so it can run effectively. PIP Violin is a violin practice subject at SMK Negeri 8 Surakarta. In its application using drill and discourse learning methods which are implemented in blended learning (offline and online).The result of this research is that the learning process runs effectively, because by combining offline and online learning the learning process runs flexibly and there is no less learning. Effective learning aspects are seen from the learning process, student responses, communicative learning, management of learning activities and student learning outcomes.Keywords: Learning Effectiveness; Learning methods; Blended Learning; Violin LearningEFEKTIVITAS METODE PEMBELAJARAN BERBASIS BLENDED LEARNING PADA MATA PELAJARAN PIP BIOLA DI SMK NEGERI 8 SURAKARTA ABSTRAK Pembelajaran di Indonesia mengalami dampak perubahan pada kegiatan pembelajaran dikarenakan adanya pandemi covid 19 yang mewabah selama kurang lebih dua tahun. Perubahan yang jelas terjadi ialah pada proses pembelajarannya ,beberapa upaya yang perlu disiapkan guru seperti menyesuaikan strategi pembelajaran dan metode pembelajaran yang sesuai. Tujuan pada penelitian ini adalah untuk mendiskripsikan penerapan pembelajaran PIP biola dengan metode berbasis blended learning sehingga dapat berjalan efektif. PIP Biola merupakan mata pelajaran paktek biola yang berada di SMK Negeri 8 Surakarta. Dalam penerapannya menggunakan metode pembelajaran drill dan ceramah yang diimplementasikan secara blended learning ( luring dan daring). Hasil dari penelitian ini adalah proses pembelajaran berjalan efektiv, karena dengan menggabungkan pembelajaran luring dan daring proses pembelajaran berjalan fleksibel dan tidak terjadi less learning. Aspek pembelajaran efektiv dilihat dari proses pembelajarannya, respon siswa, pembelajaran yang komunikatif, pengelolaan kegiatan pembelajaran dan hasil pembelajaran siswa.Kata Kunci: Efektivitas Pembelajaran; Metode Pembelajaran; Blended Learning; Pembelajaran Biola